2011
DOI: 10.1111/j.1365-2591.2011.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial leakage in root canals filled with conventional and MTA‐based sealers

Abstract: All sealers evaluated allowed bacterial leakage. The MTA-based sealers had the most leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
2
27
0
2
Order By: Relevance
“…In addition, there are studies that reported the sealing ability or biocompatibility of MTA as endodontic sealers (8)(9)(10)(11)(12)(13)(14). Furthermore, as was suggested in the recent review article by Parirokh and Torabinejad (1), various biomaterials with biological activities similar to those of MTA, such as Bioaggregate (Innovative Bioceramix, Vancouver, BC, Canada) (15) and MTA Angelus (Angelus, Londrina, PR, Brazil) (16), have been introduced and have shown good biocompatibilities and sealing abilities.…”
mentioning
confidence: 99%
“…In addition, there are studies that reported the sealing ability or biocompatibility of MTA as endodontic sealers (8)(9)(10)(11)(12)(13)(14). Furthermore, as was suggested in the recent review article by Parirokh and Torabinejad (1), various biomaterials with biological activities similar to those of MTA, such as Bioaggregate (Innovative Bioceramix, Vancouver, BC, Canada) (15) and MTA Angelus (Angelus, Londrina, PR, Brazil) (16), have been introduced and have shown good biocompatibilities and sealing abilities.…”
mentioning
confidence: 99%
“…51 Sealing ability of Epiphany was less than AH-plus and Seal Apex but better than MTA-based sealer and Active GP in one study. 52 …”
Section: Introductionmentioning
confidence: 99%
“…Quanto à solubilidade, este cimento é praticamente insolúvel, e as pesquisas têm demonstrado ser um excelente selador (ØRSTAVIK, 2005;VERSIANI et al, 2006;RESENDE et al, 2009;GARRIDO et al, 2010 Os métodos utilizados para a avaliação do pH e liberação de íons cálcio, proporcionados por cimentos endodônticos, por meio de tubos de polietileno (DUARTE et al, 2000;DUARTE et al, 2003;DUARTE et al, 2004;FERREIRA et al, 2004) -BAUZA et al, 2012;ZHOU et al, 2013;VIAPIANA et al, 2014), baixa solubilidade (SCHAFER;ZANDBIGLARI, 2003;VERSIANI et al, 2006;RESENDE et al, 2009;FLORES et al, 2011;GARRIDO et al, 2010;BORGES et al, 2012;MARÍN-BAUZA et al, 2012;VITTI et al, 2013;ZHOU et al, 2013;VIAPIANA et al, 2014), selamento apical adequado (SALEH et al, 2008;OLIVEIRA et al, 2011), boa adesão à dentina radicular (FISHER;BERZINS;BAHCALL, 2007;HARAGUSHIKU et al, 2012), baixa toxicidade (ØRSTAVIK, 2005;VERSIANI et al, 2006;RESENDE et al, 2009;GARRIDO et al, 2010;SILVA et al, 2013) e biocompatibilidade (ALMEIDA, 1997;LEONARDO et al, 1999;TAVARES et al, 2013).…”
Section: Lista De Ilustraçõesunclassified